El problema de la identidad de puntos en el control industrial (ING) - Roldán Rodríguez, Julio Roberto (2004)
In the application of precision surveys for controlling industrial machinery, networks or surveying structures based on a set of stations, which coordinates are determined on a local system by geodetic adjustment computations of the observations, are established. Angular and lineal observations are taken from the instrument station to the observed point, both materialized on the support floor of the machinery. Due to un-favored visibility conditions, it is sometimes necessary to mark the points using sighting plumbs and rods placed on tripods and centered with the aid of an optical plummet. A study of the coincidence of the point of the rod with the materialized point on the floor is done by an experiment to test the identity of both points.